ANALISIS PELAKSANAAN PIDANA KERJA SOSIAL BERDASARKAN RKUHP 2019 - Islamy, Yolanda; Rusmiati, Elis; Chandra, Erika Magdalena (DiH: Jurnal Ilmu Hukum, 2022)
This study aims to determine the Comparison of the Formulation of the Implementation of Community service order by Other Countries and the Problems of the Implementation Rules of Community service order Based on the 2019 RKUHP. The method in this study uses a normative juridical method with analytical descriptive specifications. This research is different from previous research where the study conducted in the writing of this article examines the formulation of community service order by countries that have previously implemented community service order in their criminal law rules as well as the problems that exist in the formulation of community service order in the RKUHP 2019. The formulation of community service order in the Netherlands is regulated in Art.9 jo. Art.22c-22k Criminal Code of the Netherlands) which is better known as the community service order. Until the first eight years of implementing community service order, the recidivism rate was reduced by 50%. Meanwhile, in Portugal, the rules for implementing community service order are regulated in Articles 58 and 59 of the Portuguese Criminal Code, known as Work for the Community. With the implementation of community service order, the Portuguese government has succeeded in overcoming prison overcrowding with a percentage of around 44% annually. So that the social work crime in the Netherlands and Portugal is effective as an alternatif to criminal deprivation of independence. When compared with the rules for implementing community service order in the RKUHP 2019 as a whole, they are complete and comprehensive, but there are several things that need to be underlined by legislators. For this reason, legislators need to reformulate the social work criminal rules in the RKUHP 2019 by reflecting on the formulation of community service order by countries that have previously implemented the crime in their criminal law rules. Keywords: Community Service Order, Implementation, Prospect. Abstrak Penelitian ini bertujuan untuk mengetahui Perbandingan Perumusan Pelaksanaan Pidana Kerja Sosial Oleh Negara Lain dan Analisis Aturan Pelaksanaan Pidana Kerja Sosial Berdasarkan RKUHP 2019. Metode dalam penelitian ini menggunakan metode yuridis normatif dengan spesifikasi deskriptif analitis. Penelitian ini berbeda dengan penelitian terdahulu dimana kajian yang dilakukan pada penulisan artikel ini lebih mengkaji kepada perumusan pidana keja sosial oleh negara-negara yang telah terlebih dahulu menerapkan pidana kerja sosial dalam aturan hukum pidananya serta permasalahan-permasalahan yang ada pada rumusan pidana kerja sosial dalam RKUHP 2019. Perumusan pidana kerja sosial pada Negara Belanda diatur dalam Art.9 jo. Art.22c-22k Criminal Code of the Netherlands (KUHP Belanda) yang lebih dikenal dengan community service order. Hingga delapan tahun pertama penerapan pidana kerja sosial, angka residivisme berkurang hingga 50%. Sedangkan pada Negara Portugal aturan pelaksanaan pidana kerja sosial diatur dalam Pasal 58 dan Pasal 59 KUHP Portugal yang dikenal dengan istilah Work for the Community. Dengan diterapkannya pidana kerja sosial pemerintah Portugal telah berhasil menanggulangi overcrowding lapas dengan persentase sekitar 44% setiap tahunnya. Sehingga pidana kerja sosial pada Negara Belanda dan Portugal berlaku efektif sebagai alternatif pidana perampasan kemerdekaan. Apabila dibandingkan dengan aturan pelaksanaan pidana kerja sosial dalam RKUHP 2019 secara keseluruhan sudah lengkap dan komprehensif, namun terdapat beberapa hal yang perlu digaris bawahi oleh pembentuk perundang-undangan. Untuk itu pembentuk perundang-undangan perlu merumuskan kembali aturan pidana kerja sosial dalam RKUHP 2019 dengan bercermin pada rumusan pidana kerja sosial oleh negara-negara yang telah terlebih dahulu menerapkan pidana tersebut dalam aturan hukum pidananya. Kata kunci: Analisis, Pelaksanaan, Pidana Kerja Sosial